Nucleotides flanking a conserved TAAT core dictate the DNA binding specificity of three murine homeodomain proteins. - Catron, K M (1993)
Murine homeobox genes play a fundamental role in directing embryogenesis by controlling gene expression during development. The homeobox encodes a DNA binding domain (the homeodomain) which presumably mediates interactions of homeodomain proteins with specific DNA sites in the control regions of target genes. However, the bases for these selective DNA-protein interactions are not well defined. In this report, we have characterized the DNA binding specificities of three murine homeodomain proteins, Hox 7.1, Hox 1.5, and En-1. We have identified optimal DNA binding sites for each of these proteins by using a random oligonucleotide selection strategy. Comparison of the sequences of the selected binding sites predicted a common consensus site that contained the motif (C/G)TAATTG. The TAAT core was essential for DNA binding activity, and the nucleotides flanking this core directed binding specificity. Whereas variations in the nucleotides flanking the 5' side of the TAAT core produced modest alterations in binding activity for all three proteins, perturbations of the nucleotides directly 3' of the core distinguished the binding specificity of Hox 1.5 from those of Hox 7.1 and En-1. These differences in binding activity reflected differences in the dissociation rates rather than the equilibrium constants of the protein-DNA complexes. Differences in DNA binding specificities observed in vitro may contribute to selective interactions of homeodomain proteins with potential binding sites in the control regions of target genes.